Organ‐on‐chip for advancing CAR therapy - Lightson Ngashangva; Sunil Martin (Clinical & Translational Immunology)
Abstract Despite great strides of progress, at least 60% of the responding patients relapse to CAR therapy across the blood malignancies. Off‐tumor toxicity apart from functional deficits, cytopenia and infection are the major unfavourable effect of CAR therapy. Models, which faithfully recapitulate the physiology and complexities of immunocompetent tumor microenvironment (TME), paused challenges in capturing potential off‐tumor effects of CAR therapy. Importantly, a landmark change in the legislation allows US Food and Drug Administration and New Drugs and Clinical Trial Rules in India encourages researchers to replace animal testing with cell culture approaches relevant to human system. Organ‐on‐chip (OOC) based on microfluidics technology can potentially emulate multiple biochemical and biophysical intricacies of blood and lymph flow at microscale. Nonetheless, how the evolving microfluidics technology can be enabling to real‐time testing of cell and gene is yet to be realised.